Food additives and the future of health: An analysis of the ongoing controversy on titanium dioxide. (September 2020) - Boutillier, Sophie; Fourmentin, Sophie; Laperche, Blandine
Highlights: The controversy on titanium dioxide as a food additive (E171) is associated with the technological risk of nanotechnologies. The potential carcinogenic effect of E171 ingestion creates uncertainties regarding the future of health. The controversy can be seen as a confrontation between stakeholder's organizational routines. Public decision can be considered as a compromise between stakeholders' positions. The controversy is still ongoing and necessitates adapted risk regulation. Abstract: This article studies the current controversy about the food additive titanium dioxide (E171), marked by the French decision to temporarily suspend the placing on the market of foodstuffs containing it, beginning on January 1st 2020. It aims to understand the scientific and technological content of the controversy, which implies a better assessment of the impact on health of E171. We also study its nature, understood through the identification and study of the positions of stakeholders. Finally, our third aim is to contribute to a better understanding of public decision-making. This research combines concepts used in sociology of controversy and in innovation studies (organizational routines), and is based on interviews and on the analysis of secondary data. Results show that the controversy over E171 emerged and developed when evidence of its nanoparticle content was highlighted. This leads to an analysis of the nature of controversy as a confrontation of stakeholders' organizational routines, which may contribute to a process of sensemaking, essential for decision-making in a context of uncertainty. French public decision-making does indeed appear to be a compromise between all the stakeholders' positions, where the questioning and precautionary principles play a major role. This controversy is still ongoing and is surrounded by legal and scientific uncertainties.